Eroticism and prevention of sexual transmitted disease among teenagers: how media is acting? - Mello, Glauco R; Castro, Gustavo; Reggiani, Claudete; Carvalho, Newton S (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the participation of the media in people lives, especially the young, is increasing in frequency and intensity but we have no knowledgeabout what type of information in eroticism and prevention of sexually transmitted disease (STD) is been transmitted to our adolescents. Objective:evaluate the real load of information about eroticism and prevention of STD/Aids. Methods:in an epidemiologic study were selected public and par-ticular schools from Curitiba. There were distributed questionnaires to 600 students, those from fifth to eighth grade of elementary school and fromfirst to third grade of high school with the objective of identify which media (television channels, magazines) were the most seen and read. In a sec-ond stage, the main television channels and magazines referred by the students were evaluated according to their erotic content and information aboutSTD/Aids, following a stipulated classification. The final data were computed and compared. Results:rede Globo channel was the preferred. Themost seen time schedules were from 8:00 P.M to 10 P.M. Veja was the most read magazine. In the second stage, we observed that the channel withmore erotic messages was MTV and it was also the channel containing more information about STD/Aids. The magazine that presented more eroticinformation was Veja and Capricho was the magazine with more information about STD/Aids. Conclusion: Globo TV, MTV, Veja, SuperInteressante and Capricho were the most consumed and the information about STD/Aids wasn’t enough.